Vascular Calcification, Vitamin K and Warfarin Therapy – Possible or Plausible Connection?. Issue 1 (17th July 2017) - Siltari, Aino; Vapaatalo, Heikki
Abstract: Atherosclerosis is a pathological process underpinning many cardiovascular diseases; it is the main cause of global mortality. Atherosclerosis is characterized by an invasion of inflammatory cells, accumulation of lipids and the formation of fatty streaks (plaques) which subsequently allow accumulation of calcium and other minerals leading to a disturbance in the vascular endothelium and its regulatory role in arterial function. Vascular calcification is a different process, stringently regulated mainly by local factors, in which osteoblast‐like cells accumulate in the muscular layer of arteries ultimately taking on the physiological appearance of bone. The elevated stiffness of the arteries leads to severe vascular complications in brain, heart and kidneys. Recently, evidence from animal experiments as well as clinical and epidemiological results suggests that long‐term treatment with warfarin, but not with the novel direct anticoagulants, can increase the risk or even induce vascular calcification in some individuals. Gamma‐carboxylation is an enzymatic process not only needed for activation of vitamin K but also other proteins which participate in bone formation and vascular calcification. Thus, reduced expression of the vitamin K‐dependent proteins which physiologically inhibit calcification of cellular matrix could be postulated to lead to vascular calcification. Published clinical data, describing at present a few thousand patients, need to be supplemented with controlled studies to confirm this interesting hypothesis.